A Preventive Multi-agent based Policy for Distributed Hardware Resource Balancing - Benaouda, A.; Benaouda, N. (Engineering, Technology & Applied Science Research, 2020)
The success of a business, especially a multi-site extended enterprise, depends on the good management of all its distributed resources. It is difficult for a company to be successful if it does not have a reliable and optimal management of resources by avoiding overstocking of certain resources on a site Sitem ∈ E, and at the same time, the sub-storing of the same resources on another site Sitep ∈ E. In both cases, there is a lack of profit. In this paper, we will try to resolve this situation, by the proposal of an architecture based on the cooperative multi-agent systems paradigm combined with the Contract-Net protocol. We bring in an intelligent agent whose role is to warn in advance and for each item itemi ∈ Sitem, the coming of breakdowns and stock excesses by balancing the level of inter-site availability by a flow of resources of the same itemi by calling on the other E sites whose levels are in over-storage or under-storage.